Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia - Ova Novi Irama; Suhaila Husna Samosir (Forum Kerjasama Pendidikan Tinggi, 2020)
Corporate Social Responsibility can be defined as a company's commitment to account for the impact of its operations in the social, economic and environmental dimensions, and to continue to maintain that these impacts can benefit the community and the surrounding environment. The goal is to see the influence of Corporate Social Responsibility on the company's financial performance. on the Indonesia Stock Exchange. Data is processed using simple linear regression, with a population of 45 companies and a sample of 30 samples listed on the Indonesia Stock Exchange. The results of this study indicate that the variable X (CSR) obtained t count = 0.993 with a probability value of 0.329 and based on the calculation of the t table (n-2) with a number of n = 30, the value of t table = 2.048 is obtained. t count < t table with a probability value greater than 0.05, which means that the t value obtained is not significant, with this it can be concluded that the CSR variable (X) has no significant effect on financial performance (Y)